2008
DOI: 10.1002/ejlt.200700196
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of shortenings with low‐trans fatty acids as affected by emulsifiers and storage conditions

Abstract: The quality of shortenings, such as solid fat content (SFC) and texture, strongly depends on temperature fluctuations during storage and handling. The quality of a shortening might be affected not only by temperature fluctuations but also by its chemical composition and the presence of emulsifiers. The objective of this work was to investigate the effect of emulsifier addition and storage conditions on the texture, thermal behavior and SFC of low-trans shortenings formulated with palm oil, palm kernel oil, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 22 publications
(12 reference statements)
0
23
0
3
Order By: Relevance
“…The Tonset value was lower for the SMLa A, SMLa B, and SMLa C fats than for the control fat (Table 4). This crystallization delay can be a result of the difficulties in packaging TAGs because of the differences in the chemical structure of the industrial emulsifiers such as the chain length of the esterified FA and number of esterified FAs in the glycerol molecule [6,7,25].…”
Section: Effect Of Smla On the Thermal Behavior Of Fatsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tonset value was lower for the SMLa A, SMLa B, and SMLa C fats than for the control fat (Table 4). This crystallization delay can be a result of the difficulties in packaging TAGs because of the differences in the chemical structure of the industrial emulsifiers such as the chain length of the esterified FA and number of esterified FAs in the glycerol molecule [6,7,25].…”
Section: Effect Of Smla On the Thermal Behavior Of Fatsmentioning
confidence: 99%
“…Emulsifiers are additives that are used for various purposes in the production of processed foods, such as improving the texture, volume, aeration, and homogeneity of the products [4]. Previous studies have demonstrated that emulsifiers modify the process of fat crystallization by changing the crystal habit and impeding undesirable polymorphic transitions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Other emulsifiers can be used in the stabilization of structured nanosized systems such as: monoglycerides of hydrogenated palm oil (Martini and Herrera, 2008), Tween 20 (Xin et al 2013) and Gelucires (Shimpi et al 2009;Tsai et al 2012) …”
Section: • Poloxamer 188 Is a Nonionic Surfactant With Hlb Number ~29mentioning
confidence: 99%
“…In an attempt to further understand these interactions, we conducted a study to evaluate the effect of different emulsifiers on the physical properties of shortenings with different chemical compositions and therefore different melting points. The effect of storage conditions was also analyzed and discussed (7). Some of our results are described below.…”
Section: Effect Of Emulsifiers On the Crystallization Behavior Of Lipidsmentioning
confidence: 99%